Case Study On Taylors University College's Financial Performance - Ibni, Nur Ermey (2009)
This case study is to revise the evolution of Taylor's University College from its inception as a tertiary education center to highly renowned education body from the company and the industry's perspective through case analysis, and also to perform a diagnosis of the organization to understand its current objective, vision and mission and organization structure and external factors which influences and effects the growth and the performance of Taylor's University College as a business entity as well as an education body.